To catch or cultivate - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Faced with an annual import bill of US$ 250,000 for shrimps mainly for tourist consumption the Government of Grenada is supporting attempts to establish shrimp cultivation on the island. Shrimp farming and research was started two decades ago by...